The Estimation of Power Flux of Microwave Radiation From a Negative Narrow Bipolar Pulse at Low Earth Orbit Satellite Altitude - Mohd Riduan, Ahmad; Mona Riza, Mohd Esa (Penerbit Universiti, UTeM, 2016)
In this paper, we estimate power flux densities at two points in space within the orbiting range of low Earth orbit (LEO) satellite. One point located 200 km away from the narrow bipolar pulse (NBP) emission source with angle θ = 45° and the other point located 2000 km away from the NBP emission source with angle θ = 45°. The sensitivity of the LEO satellite sensor must be larger than 10-8 W/m2/Hz at distance 200 km and 10-10 W/m2/Hz at distance 2000 km in order to be able to capture microwave radiation from NBP.